100 MHz frequency comb for low-intensity multi-photon studies: intra-cavity velocity-map imaging of xenon - Nauta, Janko; Oelmann, Jan-Hendrik (Optics letters, 2020)
We raise the power from a commercial 10 W frequency comb inside an enhancement cavity and perform multi-photon ionization of gas-phase atoms at 100 MHz for the first time, to the best of our knowledge. An intra-cavity velocity-map-imaging setup collects electron-energy spectra of xenon at rates several orders of magnitude higher than those of conventional laser systems. Consequently, we can use much lower intensities ${\sim}{{10}^{12}} \;{\rm W}/{{\rm cm}^2} $∼1012W/cm2 without increasing acquisition times above just a few seconds. The high rate and coherence of the stabilized femtosecond pulses are known to be transferred to the actively stabilized cavity and will allow studying purely perturbative multi-photon effects, paving the road towards a new field of precision tests in nonlinear physics.
Gesehen am 15.07.2020